The СС1-3 cyclotron system for non-destructive nuclear-physical methods of the element analysis - Veresov, O.L.; Gavrish, Yu.N.; Galchuck, A.V.; Grigorenko, S.V.; Grigoriev, V.I.; Emelianov, M.A.; Korolev, L.E.; Kuzhlev, A.N.; Mezhov, I.I.; Mudrolyubov, V.G.; Strokach, A.P.; Tsygankov, S.S.; et al. (Вопросы атомной науки и техники, 2013)
The СС1-3 cyclotron system is intended to be installed in the laboratory of nuclear-physical methods of the element analysis of the Vinca Institute of Nuclear Sciences, Belgrade, Serbia. The cyclotron system ensures production of a beam of protons with energy in the range from 1 to 3 MeV with a spectrum width not more than 0.1%. The equipment of the cyclotron system has been manufactured and tested on test facilities in the D.V. Efremov Institute.